INTERNATIONAL LEGAL STUDY OF THE INDONESIA-MALAYSIA REGIONAL DISPUTE ABOUT SIPADAN AND LIGITAN ISLANDS IN THE SULAWESI SEA - Kelakan, I Gusti Ngurah Kesawa Kesuma Putra; Dewi, Tjokorda Istri Diah Widyantari Pradnya (Transpublika Publisher, 2023)
The goal of this paper is to look into the background of the island disputes between Indonesia and Malaysia over Sipadan and Ligitan from the perspective of international law. In addition to the reasons, the purpose of this study is to determine the settlement process between the two countries to resolve the dispute between Sipadan and Ligitan and its implications for international law. It also aims to find out the reasons for the International Court of Justice in determining the winner of the dispute between the islands of Sipadan and Ligitan. This study uses descriptive methods, normative methods based on international law, and data collection techniques to analyze the data obtained through online search techniques and comparative research approaches. The results of this study show that the cause of the dispute between the islands of Sipadan and Ligitan originated from the absence of the two islands on the national maps of Malaysia and Indonesia, which then the two countries took steps to negotiate in international forums in resolving the dispute. It is also known that the main factor considered in determining the winner by the International Court of Justice is the comparison of the effectiveness of the management of the disputed area.